2011
DOI: 10.1002/mds.23738
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rasagiline on cognitive deficits in Parkinson's disease patients without dementia: A randomized, double‐blind, placebo‐controlled, multicenter study

Abstract: Cognitive impairment can occur at all stages of Parkinson's disease. Rasagiline is a selective monoamine oxidase type-B inhibitor that enhances central dopaminergic transmission. Dopamine is thought to be involved in certain cognitive processes such as working memory. We assessed the effects of rasagiline on cognitive deficits in cognitively impaired, nondemented patients with Parkinson's disease. This was a randomized, double-blind, placebo-controlled prospective study. Patients with Parkinson's disease recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 30 publications
3
60
0
1
Order By: Relevance
“…Further, in an 8-week study, it was found that selegiline did not have an effect on executive function using the Wisconsin Card Sorting Test (Dalrymple-Alford et al, 1995). Recently, Hanagasi et al (2011) found that compared to placebo, the MAO-B inhibitor rasagiline has a better effect on attention and executive function in nondemented PD patients. In this double blind placebo controlled multicenter trial of 48 non-demented patients with PD and cognitive impairment, significant improvement was noticed in the rasagiline group on scores of digit span backward, verbal fluency, semantic fluency, Stroop, and attentional measures (Hanagasi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, in an 8-week study, it was found that selegiline did not have an effect on executive function using the Wisconsin Card Sorting Test (Dalrymple-Alford et al, 1995). Recently, Hanagasi et al (2011) found that compared to placebo, the MAO-B inhibitor rasagiline has a better effect on attention and executive function in nondemented PD patients. In this double blind placebo controlled multicenter trial of 48 non-demented patients with PD and cognitive impairment, significant improvement was noticed in the rasagiline group on scores of digit span backward, verbal fluency, semantic fluency, Stroop, and attentional measures (Hanagasi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This issue is of particular clinical interest considering that since the time of clinical diagnosis of PD many patients present a mild cognitive impairment: is this cognitive feature worsened or improved by the prolonged dopaminergic therapy? In addition to the potential risk of inducing dyskinesia and behavioral side effects such as impulse control disorders [Weintraub et al 2010], also cognitive effects of prolonged dopaminergic treatments should be taken into account by clinicians in order to anticipate or to delay their prescription to PD patients, possibly adopting other drugs with possible effects of neuroprotection and cognitive enhancement, as the selective monoamine oxidase type-B inhibitor rasagiline [Elmer et al 2006;Hanagasi et al 2011;Jenner and Langston, 2011].…”
Section: Chronic Cognitive Effectsmentioning
confidence: 99%
“…A pilot study of donepezil for 10 PD patients with dysexecutive alterations without dementia reported improvement [15]. Rasagiline, a monoamine oxidase-B inhibitor (MAOB-I), was examined in a study of PD patients with cognitive deficits, but not PDD, and there was improvement of some measures of attention, suggesting a positive impact on executive function [16]. A longer-term study is ongoing (NCT013823420).…”
Section: Mild Cognitive Impairment and Dementia In Pdmentioning
confidence: 99%